2006
DOI: 10.1016/j.jacc.2005.12.064
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Basis for Trigger and Maintenance of Ventricular Fibrillation in the Brugada Syndrome Model

Abstract: Steep repolarization gradient in the epicardium but not endocardium develops P2R-extrasystoles in the Brugada-ECG condition, which might degenerate into VF by further depolarization and repolarization abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
90
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 123 publications
(94 citation statements)
references
References 37 publications
3
90
1
Order By: Relevance
“…This has been linked to an increased risk of cardiac death [151] and, in particular, to a higher risk of arrhythmogenicity in short QT, long QT and Brugada syndromes [152][153][154][155]. In Brugada syndrome, for instance, dispersion of repolarization is thought to be caused by an abbreviation of the APD of the right ventricular epicardium due to loss of the action potential dome [156]. Then, a region of depolarized tissue (during calcium current entrance, or phase-2 of the AP) can re-excite adjacent regions that exhibit shorter action potential duration (APD) [130], producing an extrasystole which can eventually initate phase-2 reentry (see Figure 17).…”
Section: Gradients Of Electrophysiological Propertiesmentioning
confidence: 99%
“…This has been linked to an increased risk of cardiac death [151] and, in particular, to a higher risk of arrhythmogenicity in short QT, long QT and Brugada syndromes [152][153][154][155]. In Brugada syndrome, for instance, dispersion of repolarization is thought to be caused by an abbreviation of the APD of the right ventricular epicardium due to loss of the action potential dome [156]. Then, a region of depolarized tissue (during calcium current entrance, or phase-2 of the AP) can re-excite adjacent regions that exhibit shorter action potential duration (APD) [130], producing an extrasystole which can eventually initate phase-2 reentry (see Figure 17).…”
Section: Gradients Of Electrophysiological Propertiesmentioning
confidence: 99%
“…4,15 A large increase in TDR is likely to be arrhythmogenic because the dispersion of repolarization and refractoriness occurs over a very short distance (the width of the ventricular wall), creating a steep repolarization gradient. 16,17 It is the steepness of the repolarization gradient rather than the total magnitude of dispersion that determines its arrhythmogenic potential. Apicobasal or interventricular dispersion of repolarization is less informative because it may or may not be associated with a steep repolarization gradient and thus may or may not be associated with arrhythmic risk.…”
mentioning
confidence: 99%
“…15) The cellular basis of Brugada syndrome has been attributed to depression or loss of the action potential dome in the RV epicardium, which creates a transmural voltage gradient that is responsible for the ST-segment elevation in Brugada syndrome and repolarization heterogeneity of the RV. 26,27) It was also shown in dogs that extrasystolic activity due to phase 2 reentry can arise in the intact wall of the right ventricle and serve as the trigger for ventricular tachycardia/VF. 27,28) Clinical studies on the pathogenesis of Brugada syndrome also revealed the presence of a deeply notched action potential in the RV epicardium and abnormal RV action potential restitution properties.…”
Section: )mentioning
confidence: 99%